KRIMINALITAS DALAM CERITA PENDEK â€œTÃ–DLICHER SCHNEEâ€ KARYA FELIX DAN THEO - CHRISTINA LEJA, MARIA (IDENTITAET, 2017)
Literatur is an expression of the author’s feelings about what he experienced and also about the picture of the reality of people’s lives around the author. The short story of “Tödlicher Schnee” by Felix and Theo are among the short story that tell about crime. The research on criminality in short story “Tödlicher Schnee” by Felix and Theo refers to two problems : what criminal acts exist in the short story “Tödlicher Schnee” by Felix and Theo. Based on the formulation of the problem it can be cocluded that the purpose of this research is to describe the criminal acts that exist in the short story “Tödlicher Schnee” by Felix and Theo and also describe the motive of causing crime in the short story “Tödlicher Schnee” by Felix and Theo. The type of research ist qualitative research. Sources of data used are short story “Tödlicher Schnee” by Felix and Theo. The data in this study are words and phrases of conversation quotations in the short story “Tödlicher Schnee” by Felix and Theo. The results of this study reveal that (1) the criminal acts that exist in the short story “Tödlicher Schnee” by Felix and Theo is murder, extortion, terror and murder (abortion); (2) the motive of crime in the short story “Tödlicher Schnee” by Felix and Theo is an aggressive crime of revenge and hated. Keywords: Sociology of Literature, Crime.